2006
DOI: 10.1002/neu.20251
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic pruning of the medial amygdala during pubertal development of the male Syrian hamster

Abstract: The medial amygdala (Me), a brain region essential for mating behavior, changes in size during puberty. In pre-, mid-, and late pubertal (21, 35, and 49 days of age) male Syrian hamsters, we examined neuronal structure in Me and protein levels of spinophilin and synaptophysin in the amygdaloid complex for evidence of synaptic plasticity coincident with behavioral and physiological development. Body weight, testes weight, and testosterone levels increased during puberty. Mounting behavior, including ectopic, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 67 publications
5
86
1
1
Order By: Relevance
“…Differences between that study and ours are probably attributable to the choice of markers, spinophilin in our study, and synaptophysin in that of Andersen and Teicher (2004). These two markers do not exist in the same subcellular compartment (Choi et al 2003) and in fact, a study by Zehr et al found opposite pubertal changes in spinophilin (decrease) and synaptophysin (increase) in the amygdala of developing male hamsters (Zehr et al, 2006). …”
Section: Hippocampal Plasticity and Pubertycontrasting
confidence: 77%
See 2 more Smart Citations
“…Differences between that study and ours are probably attributable to the choice of markers, spinophilin in our study, and synaptophysin in that of Andersen and Teicher (2004). These two markers do not exist in the same subcellular compartment (Choi et al 2003) and in fact, a study by Zehr et al found opposite pubertal changes in spinophilin (decrease) and synaptophysin (increase) in the amygdala of developing male hamsters (Zehr et al, 2006). …”
Section: Hippocampal Plasticity and Pubertycontrasting
confidence: 77%
“…Although the mechanisms for these alterations in cognitive function are poorly understood, they may be due to developmental changes in synaptic plasticity that occur across the pubertal period. Consistent with this, reports show that synaptic density and/or dendritic spine number decrease during the transition from puberty to adulthood, as shown in monkey cortex (somatosensory: Zecevic & Rakic, 1991;prefrontal: Woo et al, 1997;visual: Bourgeois & Rakic, 1993) hamster medial amygdala (Zehr et al, 2006), and mouse hippocampus (Meyer et al, 1978).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Indeed, we found a decrease in the number of astrocytes in the rat amygdala after 3 weeks of age. Other studies have suggested a decrease in neuropil volume in the medial amygdala during puberty in the rat (Zehr et al, 2006). Similarly, a tracttracing study, using both retrograde and anterograde tracers, has shown that mPFC projections to the basal and accessory basal nuclei decrease between P25 and P90 in rats (Cressman et al, 2010).…”
Section: Second Stage: Myelinationmentioning
confidence: 81%
“…During adolescence, synaptic connections and neural circuits are still remarkably plastic. For example, neuron number in the prefrontal cortex differs in adolescent and adult rats (Markam et al, 2007), and neurons of the medial amygdala differ in structure among pre-, mid-, and late adolescent male hamsters (Zehr et al, 2006). Furthermore, adolescent rodents show differential responsiveness to anxiogenic situations, which is directly related to different effects of neurosteroids on cell excitability in adolescents and adults (Shen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%